APPROACH TO THE BRAZILIAN AND EUROPEAN LEGISLATION ON GEOGRAPHICAL INDICATION - Almeida, Sabrina Cantarelli; Dörr, Andrea Cristina; Guse, Jaqueline Carla; Rossato, Marivane Vestena; Sidali, Katia Laura; Marchese, Aldo (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The adoption of the Geographical Indication (GI) is associated with the tradition of knowledge and food. Bearing in mind that the studies on this topic are still very recent and scarce in Brazil aimed to conduct a literature review of existing law sand norms in Brazil and in Europe on the aspect of geographical indication. We used the qualitative method, through a descriptive study and using the literature search. It is observed that concerns about Geographical Indications are the oldest in the countries of the European Union, and European legislation brings strong regulation son the subject. In Brazil this vision brought by the Geographical Indication is still very recent and walks to a greater appreciation and regulation of such products. It follows GIs bring extremely positive contributions to local economies and to regional dynamics, providing the real meaning of value creation, acting as a kind of certification with defined attributes, ensuring their consistency with prescribed standards.